2020
DOI: 10.3389/fpsyg.2020.560828
|View full text |Cite
|
Sign up to set email alerts
|

The Role of News Consumption and Trust in Public Health Leadership in Shaping COVID-19 Knowledge and Prejudice

Abstract: The novelty of COVID-19 has created unique challenges to successful public health efforts because it has required the public to quickly learn and formulate knowledge and attitudes about the virus as information becomes available. The need to stay apprised of new information has also created a critical role for mass media and public institutions in shaping the public's knowledge of, attitudes about, and responses to the unfolding pandemic. In this study, we examine how media consumption and reliance on specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 29 publications
6
84
0
10
Order By: Relevance
“…In our study, the trigger event for a record number of tweets was the announcement that the reporting of COVID-19 hospital data would be sent to the Trump administration rather than the CDC, and the dissenting voice dominated the discussion on this topic. To a large extent, this finding is consistent with the findings of a survey study that showed that Americans’ average trust rating for the CDC was significantly higher than that for President Trump [ 40 ]. The significance of positive public perception of public health agencies has been receiving increasing recognition [ 9 , 10 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the trigger event for a record number of tweets was the announcement that the reporting of COVID-19 hospital data would be sent to the Trump administration rather than the CDC, and the dissenting voice dominated the discussion on this topic. To a large extent, this finding is consistent with the findings of a survey study that showed that Americans’ average trust rating for the CDC was significantly higher than that for President Trump [ 40 ]. The significance of positive public perception of public health agencies has been receiving increasing recognition [ 9 , 10 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…The significance of positive public perception of public health agencies has been receiving increasing recognition [ 9 , 10 , 51 , 52 ]. It has been found that greater trust in the CDC was associated with increased knowledge and a lower acceptance of misinformation [ 40 ]. The widespread dissemination of the CDC guidelines, as well as the fast speed at which they were circulated, on the one hand reflected the public's urgent need for information as discussed above and, on the other hand, it reflected their trust in the CDC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Prior studies examining the associations between COVID-19 information sources and attitudes towards COVID-19 messaging have elucidated differences in trust of COVID-19 information and self-reported adherence to COVID-19 preventive behaviours among men, individuals who are unemployed or retired, and adults who politically identify as Republican. [27][28][29][30] While we were unable to adjust for political affiliation within our analyses due to the lack of data availability within the COVID-19 Impact Survey, research shows that NH whites, men and individuals residing in rural areas more frequently identify their political affiliation as Republican. 31 32 Our observed geographic disparities in COVID-19 preventive behaviours may also be a reflection of variability in state or local policies regarding COVID-19 preventive behaviours across the individuals residing in US states and counties that have implemented mandatory COVID-19 preventive behaviours, including stay-at-home orders, social distancing and mandatory mask use in public, are more likely to exhibit positive individual-level COVID-19 preventive behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…While a series of studies made significant contributions along these lines, the majority of existing studies analyzed data collected before the middle of April 2020 [29][30][31][32][33][34][35][36][37][38][39]. In addition, there have been scarce social media studies with a focus on the CDC during the COVID-19 pandemic [6], the main source for evidence-based information about the pandemic [40]. To fill the gaps in knowledge after the WHO's declaration of a pandemic, we used text mining methods to analyze COVID-19-related tweets about the CDC from March 11 to August 14, 2020.…”
Section: Introductionmentioning
confidence: 99%